2019
DOI: 10.1177/2309499019839616
|View full text |Cite
|
Sign up to set email alerts
|

Hand-mixed vancomycin versus commercial tobramycin cement revisited: A study on mechanical and antibacterial properties

Abstract: Arthroplasty-related infection has grown worldwide. Revision procedures for infection are associated with longer operating time, superior amounts of blood loss, and substantial economic encumbrance. To overcome cost, many surgeons opt for hand-mixed vancomycin into the bone cement. The objective of this research was to assess the biomechanical strength and antibacterial properties of hand-mixed vancomycin bone cement at different concentrations with commonly used industrial preblended antibiotic bone cement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Other bone cement additives that have been put to test are microhydroxyapatite, -magnesium oxide, -barium sulphate and -silica particles [15,36,37], as well as methacrylate crosslinkers ethylene glycol-dimethacrylate (EG-DMA) [15,57,58] or hydroxyethyl methacrylate (HEMA) [15,59], and finally, triethylene glycol-dimethacrylate (TEG-DMA) [15,60,61]. PMMA cement supplementation with vancomycin was assessed in the study by Ajit Singh et al [30], who concluded that even a 2 g addition of the drug per a 40 g container of cement (5% by weight) significantly affects the degradation of the three-point bending flexural strength. The antibiotic, supplemented in the form of a powder acts as an inclusion that causes stress build-up and as a result the weakening of the cement [30,62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other bone cement additives that have been put to test are microhydroxyapatite, -magnesium oxide, -barium sulphate and -silica particles [15,36,37], as well as methacrylate crosslinkers ethylene glycol-dimethacrylate (EG-DMA) [15,57,58] or hydroxyethyl methacrylate (HEMA) [15,59], and finally, triethylene glycol-dimethacrylate (TEG-DMA) [15,60,61]. PMMA cement supplementation with vancomycin was assessed in the study by Ajit Singh et al [30], who concluded that even a 2 g addition of the drug per a 40 g container of cement (5% by weight) significantly affects the degradation of the three-point bending flexural strength. The antibiotic, supplemented in the form of a powder acts as an inclusion that causes stress build-up and as a result the weakening of the cement [30,62].…”
Section: Discussionmentioning
confidence: 99%
“…PMMA cement supplementation with vancomycin was assessed in the study by Ajit Singh et al [30], who concluded that even a 2 g addition of the drug per a 40 g container of cement (5% by weight) significantly affects the degradation of the three-point bending flexural strength. The antibiotic, supplemented in the form of a powder acts as an inclusion that causes stress build-up and as a result the weakening of the cement [30,62]. The study also tested the antibacterial properties of the antibiotic-supplemented cement: The increase in the amount of antibiotic in the mix, except for not contributing to any improvement in the bactericidal effectiveness, furthermore accelerated its mechanical degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison between spacers loaded with the combination of gentamicin and vancomycin and spacers loaded with gentamicin alone has shown the higher antibacterial efficacy of the former. Finally, the antibiotic can be industrially blended into the pre-polymerized PMMA or can be manually added by a surgeon at the surgical site [17,51]. Figure 4 reports the trend of cumulative release of gentamicin-containing Palacos ® R + G (commercial sample) and Palacos ® R + GM (sample with gentamicin manually (M) added), together with the respective images of inhibition zones [16].…”
Section: Cement With Antibacterial Activity: Antibiotic-loaded Bonmentioning
confidence: 99%
“…The utilization of antibiotic-laden cement (ALC), which delivers antibiotics directly into the joint, has become a common adjunct to treat and prevent PJI in arthroplasty patients [3]. Commercially available single antibiotic cements typically contain an aminoglycoside such as tobramycin to prevent infections by Gram negative organisms [4]. However, they have poor coverage of some Gram positive organisms, which comprise 86%-90% of all PJIs [5].…”
mentioning
confidence: 99%